Beatrice en Demian de Hermann Hesse - Vilella, Eduard (Cuadernos de Filología Italiana, 2007)
One of the chapters of Demian by Hermann Hesse presents a feminine figure that the main character secretly calls Beatrice. Departing from this episode’s narrative implications in the system of the novel, this article aims to emphasize the potential meaning of the reference to Dante’s work in order to add it to other more immediate elements such as the implicit echoes of Jungian psychology, often used in critical literature, or the text’s explicit reference to pre-Raphaelite aesthetics.